Answer:
x
Step-by-step explanation:
-2x²(x – 5) + x(2x² – 10x) + x
The simplest for of the above equation can be obtained as follow:
-2x²(x – 5) + x(2x² – 10x) + x
Rearrange
x(2x² – 10x) – 2x²(x – 5) + x
Factorise
x.2x(x – 5) – 2x²(x – 5) + x
2x²(x – 5) – 2x²(x – 5) + x
Carry out the minus (–) operation
=> x
Therefore, the simplest form of expressing -2x2(x – 5) + x(2x2 – 10x) + x is x.
According to above figure, the angles (8x - 20)° and (5x + 37)° are pairs of vertical opposite angles, so
Simplify the first numerator first
-2(x+1)
-2x-2
Then you can set up an equation using cross multiplication
5(-2x-2)= 3x
Simplify and solve
-10x-10=3x
-10=13x
-10/13=x
Final answer: x=-10/13
Answer:
7, 9, 17
Step-by-step explanation:
The sum of the two smallest numbers has to form a number larger that the largest number, and 7 + 9 = 16 which is less than 17.
Answer:
1280
Step-by-step explanation:
32x4=128
320x4=1280